Catalytic Cleavage of Amide C−N Bond: Scandium, Manganese, and Zinc Catalysts for Esterification of Amides. Issue 4 (11th September 2019) - Mashima, Kazushi; Nishii, Yuji; Nagae, Haruki
Abstract: Amide C−N bonds are thermodynamically stable and their fission, such as by hydrolysis and alcoholysis, is considered a long‐challenging organic reaction. In general, stoichiometric chemical transformations of amides into the corresponding esters and acids require harsh conditions, such as strong acids/bases at a high reaction temperature. Accordingly, the development of catalytic reactions that cleave not only primary and secondary amides, but also tertiary amides in mild conditions, is in high demand. Herein, we surveyed typical stoichiometric transformations of amides, and highlight our recent achievements in the catalytic esterification of amides using scandium, manganese, and zinc catalysts, together with some recent catalyst systems using late‐transition metal reported by other groups. Abstract : Catalytic esterification of thermodynamically stable amides via C−N bond cleavage was achieved by transition metal catalysts containing scandium, manganese, and zinc. These catalysts activated not only carbonyl moiety of the amides but also alcohols. Kinetic studies of manganese catalyst suggesting that two metal sites might be inevitably required to show catalytic cleavage of the amide C−N bond, which is most relevant to the functional model of metalloenzymes.